Approaching the environmental Kuznets curve: Empirical evidence from turkey - Ugur, Ahmet; Gultekin, Esma (Statistical Economic and Social Research and, 2018)
This study investigated the important relationship between environmental factors and economic growth within the context of adaptation to the environment. We generated a Kuznets curve based on the original Kuznets (1995) curve for Turkey’s economy for the period 1960–2011, using the carbon dioxide emissions, energy consumption and per capita GDP variables. A time series analysis was applied to test the existence of a long-run relationship between the series and the coefficient definitions of the variables were made. The results obtained were parallel to the Kuznets curve for Turkey’s economy and the reverse approach was accepted and the structural break analyzes applied in the study are important in terms of Turkey's economy. © 2018, Statistical Economic and Social Research and. All rights reserved.
Keywords: CO2 emissions; Cointegration; Energy consumption; Environmental Kuznets curve; Pollution